Metallurgy in ancient Ecuador : a study of the collection of archaeological metallurgy of the Ministry of Culture, Ecuador - Lleras Pérez, Roberto, (Archaeopress preColumbian archaeology ;, 2015)
Metallurgical activity was present in Ecuador from at least 1500 BC; by around the beginning of the Common Era metallurgical manufacture and use had extended to most of the Costa and Sierra. Regional styles soon evolved giving rise to high levels of technical craftsmanship and to shaping particular iconographic and decorative patterns. Copper, gold, silver and platinum were mined, processed and converted into thousands of ornaments, offerings, tools and weapons extensively used both by elites and by the common people. This work discusses this topic.